Preparation method and application of two-dimensional composite material

By using MgAl LDH/MXene two-dimensional composite material as the separator barrier layer in lithium-sulfur batteries, the problem of low electrochemical performance of lithium-sulfur batteries is solved, and the rapid transmission of lithium ions and rapid redox reaction of polysulfides is achieved, which is extended. Battery life and improve electrochemical performance.

CN119240768APending Publication Date: 2025-01-03GUIZHOU UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411367318.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The low electrochemical performance and short life of lithium-sulfur batteries are mainly due to the poor conductivity of sulfur, the shuttle effect of polysulfides between electrodes and the lithium ion diffusion barrier. Commonly used polypropylene separators cannot be used due to their hydrophobicity and low porosity. Effective solution.

Method used

Using MgAl LDH/MXene two-dimensional composite material as the barrier layer of lithium sulfur battery separator, it is prepared by ultrasonic dispersion, magnetic stirring and anhydrous ethanol washing in formamide to form a two-dimensional meter with high specific surface area and excellent conductivity. Dimensional composite materials enhance the wettability of the electrolyte and polysulfide conversion, and alleviate the volume expansion during the circulation of lithium-sulfur batteries.

Benefits of technology

It realizes rapid transmission of lithium ions and rapid redox reaction of polysulfides, extends the service life of lithium-sulfur batteries, and improves electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240768A_ABST
    Figure CN119240768A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a two-dimensional composite material. The preparation method comprises the following steps: adding MXene into formamide, carrying out ultrasonic dispersion to obtain an MXene formamide dispersion liquid, then adding MgAl LDH into the MXene formamide dispersion liquid, carrying out magnetic stirring, washing with absolute ethyl alcohol, and carrying out vacuum drying to obtain a two-dimensional composite material which is marked as MgAl LDH / MXene. The two-dimensional composite material is used for a lithium-sulfur battery diaphragm barrier layer so as to inhibit the shuttle effect of polysulfide. The preparation method is simple and environment-friendly, and the prepared MgAl LDH / MXene two-dimensional composite material is high in specific surface area, has strong affinity to polysulfide, can promote rapid transmission of lithium ions, can provide an instant electron conduction way for adsorbed polysulfide, is applied to a diaphragm barrier layer of a lithium-sulfur battery, and has a good application prospect. The wettability of the electrolyte on the diaphragm and the conversion of polysulfide are enhanced, the problem of volume expansion in the cycle process of the lithium-sulfur battery is relieved, and the redox reaction kinetics is accelerated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation method of a composite material and application thereof, in particular to a preparation method of a two-dimensional composite material and application thereof. Background Art

[0002] Lithium-sulfur batteries are one of the most promising next-generation batteries due to their theoretically high specific capacity and energy density. However, problems such as poor sulfur conductivity, the "shuttle" of polysulfides between electrodes, and the density difference between sulfur and its reduction products still restrict their application development. The performance and life of batteries are closely related to the diaphragm. The commonly used polypropylene diaphragm (PP) has low electrochemical performance of lithium-sulfur batteries due to its hydrophobic structure and low porosity in morphology. Therefore, people usually solve the above problems by modifying and processing the battery diaphragm. By coating some inorganic nanoparticles such as silicon dioxide and titanium dioxide with good hydrophilicity and high specific surface area on the surface of PP diaphragm, the hydrophilicity of the diaphragm can be improved, but the effect of coating a single material is not significant and will also affect the service life of the battery.

[0003] In summary, in order to solve the above technical problems, the present invention provides a method for preparing a two-dimensional composite material and application thereof. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of a two-dimensional composite material. The present invention has a simple preparation method and is environmentally friendly. The prepared MgAl LDH / MXene two-dimensional composite material has a high specific surface area. The abundant hydroxyl groups on the MgAl LDH make it have a strong affinity for polysulfides, and because it can reduce the lithium ion diffusion barrier, lithium ions can be quickly transmitted. At the same time, with the excellent conductivity of MXene, an immediate electronic conduction path is provided for the adsorbed polysulfides. The application of the MXene in the barrier layer of the lithium-sulfur battery diaphragm enhances the wettability of the electrolyte to the diaphragm and the conversion of polysulfides, alleviates the volume expansion problem during the cycle of the lithium-sulfur battery, and thus accelerates the redox reaction kinetics.

[0005] The technical solution of the present invention is a method for preparing a two-dimensional composite material, which comprises adding MXene to formamide, ultrasonically dispersing to obtain a MXene formamide dispersion, then adding MgAl LDH to the MXene formamide dispersion, magnetically stirring, washing with anhydrous ethanol, and vacuum drying to obtain a two-dimensional composite material, which is recorded as MgAl LDH / MXene.

[0006] In the preparation method of the aforementioned two-dimensional composite material, 0.1-0.2 g of MXene is added to 100-200 mL of formamide, ultrasonically dispersed for 30-90 minutes to obtain a MXene formamide dispersion, and then 0.1-0.2 g of MgAl LDH is added to 100-200 mL of MXene formamide dispersion, magnetically stirred for 8-15 hours, washed with anhydrous ethanol 7-15 times, and vacuum dried at 40-80°C for 12-36 hours to obtain a two-dimensional composite material, recorded as MgAl LDH / MXene.

[0007] In the preparation method of the aforementioned two-dimensional composite material, 0.16 g of MXene is added to 160 mL of formamide, ultrasonically dispersed for 60 minutes to obtain a MXene formamide dispersion, and then 0.16 g of MgAl LDH is added to the 160 mL of MXene formamide dispersion, magnetically stirred for 12 hours, washed with anhydrous ethanol 12 times, and vacuum dried at 60°C for 24 hours to obtain a two-dimensional composite material, recorded as MgAlLDH / MXene.

[0008] In the aforementioned method for preparing the two-dimensional composite material, the MgAl LDH is prepared by the following method:

[0009] 0.5-0.8 g of magnesium aluminum hydrotalcite, 20-45 g of sodium chloride and 60-100 μL of 10-15 mol / L hydrochloric acid solution were added to 400-500 mL of deionized water, stirred magnetically for 20-28 h, washed with deionized water for 7-12 times, and freeze-dried at -50--30 ° C for 12-48 h to obtain MgAl-Cl - LDH powder;

[0010] 0.4~0.6g MgAl-Cl - LDH and 6.5-10.5 g sodium nitrate were added to 400-500 mL deionized water, stirred for 12-36 h, washed with deionized water 7-12 times, and freeze-dried at -50--30 °C for 12-36 h to obtain MgAl-NO3 - LDH powder;

[0011] 0.1~0.3g MgAl-NO3 - Add 150-250 mL of formamide to LDH and perform ultrasonic stripping for 12-36 h to obtain MgAlLDH.

[0012] In the aforementioned method for preparing the two-dimensional composite material, the MgAl LDH is prepared by the following method:

[0013] 0.6 g of magnesium aluminum hydrotalcite, 32.9 g of sodium chloride and 85 μL of 12 mol / L hydrochloric acid solution were added to 450 mL of deionized water, magnetically stirred for 24 h, washed with deionized water 9 times, and freeze-dried at -45 °C for 24 h to obtain MgAl-Cl - LDH powder;

[0014] 0.5 g MgAl-Cl - LDH and 8.5 g sodium nitrate were added to 450 mL deionized water, stirred for 24 h, washed with deionized water 9 times, and freeze-dried at -45 °C for 24 h to obtain MgAl-NO3 - LDH powder;

[0015] 0.2g MgAl-NO3 - Add 200 mL of formamide to LDH and perform ultrasonic stripping for 24 h to obtain MgAl LDH.

[0016] In the above-mentioned preparation method of the two-dimensional composite material, the MXene is prepared by the following method: at 2 to 5°C, 2 to 4 g of lithium fluoride and 20 to 40 mL of 10 to 15 mol / L hydrochloric acid solution are placed in a polytetrafluoroethylene reactor, and magnetic stirring is performed for 15 to 45 minutes to react, and then 2 to 4 g of titanium carbide aluminum powder is added to the reactor within 25 to 35 minutes, and after etching for 0.5 to 1.5 hours, the temperature is raised to 30 to 45°C, and the reaction is performed for 12 to 48 hours to obtain a mixed solution; the mixed solution is firstly heated with 100 to 200 mL of 0. The product was pickled with 5-1.5 mol / L hydrochloric acid, centrifuged at 2500-4500 r / min for 0.5-2 min, then washed and centrifuged with deionized water under the same conditions until the pH value of the solution became 5-7. The upper solution was first introduced with nitrogen for 0.5-2 h, and then ice-bathed for 30-80 min under the protection of nitrogen. Then, the product was centrifuged at 2500-4500 r / min for 0.5-2 h, the upper liquid was collected, and freeze-dried at -50--30 °C for 24-72 h to obtain MXene.

[0017] In the preparation method of the aforementioned two-dimensional composite material, the MXene is prepared by the following method: at 3°C, 30mL of 12mol / L hydrochloric acid solution of 3g lithium fluoride is placed in a polytetrafluoroethylene reactor, magnetically stirred for 30min, and then 3g of titanium carbide aluminum powder is added to the reactor within 30min. After etching for 1h, the temperature is raised to 36°C and reacted for 24h to obtain a mixed solution; the mixed solution is first pickled with 150mL of 1mol / L hydrochloric acid, centrifuged at 3500r / min for 1min, and then washed and centrifuged with deionized water under the same conditions until the pH value of the solution becomes 7, the upper layer solution is first introduced with nitrogen for 1h, and under the protection of nitrogen, ice bath ultrasound is performed for 50min, and then centrifuged at 3500r / min for 1h, the upper layer liquid is collected, and freeze-dried at -40°C for 48h to finally obtain MXene.

[0018] The application of the aforementioned two-dimensional composite material is that the two-dimensional composite material is used for the barrier layer of the lithium-sulfur battery separator to inhibit the shuttle effect of polysulfide.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention adds MXene to formamide and performs ultrasonic dispersion to obtain a MXene formamide dispersion. The reason for adding MXene to formamide instead of water is to avoid that when MXene and MgAl LDH are composited, MgAl LDH is first reconstructed with water molecules. MgAl LDH is added to the MXene formamide dispersion and the two are evenly mixed by magnetic stirring force to achieve electrostatic assembly. Anhydrous ethanol is used for washing to remove the solvent, and then the material is dried under vacuum to remove moisture and isolate oxygen to prevent oxidation of the material. Finally, a two-dimensional composite material is obtained, which is recorded as MgAl LDH / MXene. The preparation method is simple and the cycle is short.

[0021] 2. The present invention adds 0.5-0.8g of magnesium aluminum hydrotalcite, 20-45g of sodium chloride and 60-100μL of 10-15mol / L hydrochloric acid solution to 400-500mL of deionized water, and stirs magnetically for 20-28h. The CO3 between the magnesium aluminum hydrotalcite layers is removed by the magnetic stirring force. 2- Replaced with Cl - , then washed with deionized water 7 to 12 times to remove the solvent, and freeze-dried at -50 to -30 ° C for 12 to 48 hours to remove excess water to obtain MgAl-Cl - LDH powder;

[0022] 0.4~0.6g MgAl-Cl -LDH and 6.5-10.5 g of sodium nitrate were added to 400-500 mL of deionized water and stirred for 12-36 h. The MgAl-Cl - Cl between LDH layers - Replaced with NO3 - , washed with deionized water for 7 to 12 times, freeze-dried at -50 to -30 ° C for 12 to 36 hours to remove excess water, and obtained MgAl-NO3 - LDH powder;

[0023] For magnesium-aluminum hydrotalcite, the interlayers have CO3 2- The anions of the layer are difficult to be stripped by formamide due to the electrostatic interaction between the layers, and the inorganic anions between the layers have an exchange order, and the order of exchange capacity is: CO3 2- >Cl - >NO3 - Utilizing this property, CO3 can be brought into the interlayer of magnesium-aluminum hydrotalcite 2- The anion is replaced by NO3 - , which is beneficial to Mg Al-NO3 - The interlayer spacing of LDH is enlarged by formamide molecules to facilitate peeling.

[0024] 0.1~0.3g Mg Al-NO3 - Add 150-250 mL of formamide, Mg Al-NO3 - After the interlayer spacing of LDH is enlarged by formamide molecules, a swelling phase is formed. Ultrasonic peeling takes 12 to 36 hours. The lateral shear force generated by ultrasound slowly peels off the layers to obtain two-dimensional MgAl LDH. In addition, low-cost magnesium-aluminum hydrotalcite is used as the raw material, the preparation cycle is short, and the method is simple.

[0025] 3. The present invention uses titanium aluminum carbide powder to etch MXene through hydrofluoric acid and lithium salt. The method is simple to operate and has a short preparation cycle. Specifically, at 2-5°C, 2-4g of lithium fluoride and 20-40mL of 10-15mol / L hydrochloric acid solution are placed in a polytetrafluoroethylene reactor, and magnetic stirring is performed for 15-45min. The lithium fluoride and hydrochloric acid are reacted by magnetic stirring force to generate hydrofluoric acid and lithium salt to etch the Al atoms in titanium aluminum carbide (MAX). Then 2-4g of titanium aluminum carbide powder is added to the reactor within 25-35min. The reaction of titanium aluminum carbide and hydrofluoric acid will release a lot of heat, so the MXene is etched at low temperature to ensure mild etching conditions and experimental safety. After etching for 0.5 to 1.5 hours, the temperature is raised to 30 to 45°C, and the mixture is reacted for 12 to 48 hours to obtain a mixed solution. Raising the temperature is beneficial to the change in the MXene interlayer spacing, and the metal Al atoms are easier to remove. The mixed solution is first pickled with 100 to 200 mL of 0.5 to 1.5 mol / L hydrochloric acid, centrifuged at a speed of 2500 to 4500 r / min for 0.5 to 2 minutes, and then washed and centrifuged with deionized water under the same conditions until the pH value of the solution becomes 5 to 7. The purpose of pickling and centrifuging with hydrochloric acid is to clean the unreacted lithium fluoride and lithium salt, and the purpose of washing with deionized water is to separate the MXene in the suspension. Centrifugation at a speed of 2500 to 4500 r / min is to obtain a single layer or a few layers of MXene. When the pH value reaches the range of 5 to 7, the MXene is completely separated. Subsequently, the mixture was washed and centrifuged with deionized water under the same conditions until the pH value of the solution became 5-7. The upper layer of the solution was first introduced with nitrogen for 0.5-2 hours. Under the protection of nitrogen, ice bath ultrasound was performed for 30-80 minutes to peel the MXene from the stacked state into a few layers or a single layer structure. The MXene was then centrifuged at a speed of 2500-4500 r / min for 0.5-2 hours, and the upper layer of liquid was collected to obtain pure liquid MXene. The bottom product was the incompletely etched MXene and lithium salt, which was freeze-dried at -40°C for 48 hours to remove moisture to obtain MXene.

[0026] 4. The two-dimensional composite material prepared by the present invention is used for the barrier layer of the lithium-sulfur battery diaphragm to inhibit the shuttling effect of polysulfides. The two-dimensional composite material has a high specific surface area, can accommodate polysulfides, and reduce the shuttling of polysulfides; it can reduce the effect of lithium ion diffusion barrier and enable rapid lithium ion transmission; it can provide an immediate electron conduction pathway for adsorbed polysulfides. The combination of the two forms complementary advantages and ensures rapid electrochemical redox reaction kinetics.

[0027] 5. The present invention has a simple preparation method and is environmentally friendly. The raw materials are abundant, the preparation cycle is short, and the yield is high. The prepared MgAlLDH / MXene composite material is in a two-dimensional sheet shape with a thickness of only 6 to 7 nm, so it has a high specific surface area and has great application prospects in adsorption and catalysis, especially in lithium-sulfur batteries. The positively charged layers of MgAl LDH and the abundant hydroxyl groups on the layers make it have a strong affinity for polysulfide (S8 2- , S6 2- ,S4 2- It has a strong affinity for lithium ions and can reduce the diffusion barrier of lithium ions to enable rapid lithium ion transmission. At the same time, the surface of MXene is rich in oxygen-containing functional groups (-F, -OH, -O), which makes it have excellent conductivity and provides an immediate electronic conduction pathway for adsorbed polysulfides. The application of this material in the barrier layer of lithium-sulfur battery separator enhances the wettability of the electrolyte to the separator and the conversion of polysulfides, alleviates the volume expansion problem during the cycle of lithium-sulfur batteries, and thus accelerates the redox reaction kinetics.

[0028] In summary, the present invention has a simple preparation method and is environmentally friendly. The prepared MgAl LDH / MXene two-dimensional composite material has a high specific surface area. The abundant hydroxyl groups on MgAl LDH give it a strong affinity for polysulfides, and because it can reduce the lithium ion diffusion barrier, lithium ions can be quickly transmitted. At the same time, combined with the excellent conductivity of MXene, an immediate electron conduction pathway is provided for the adsorbed polysulfides. The application of the present invention to the barrier layer of the lithium-sulfur battery diaphragm enhances the wettability of the electrolyte to the diaphragm and the conversion of polysulfides, alleviates the volume expansion problem during the cycle of the lithium-sulfur battery, and thus accelerates the beneficial effect of the redox reaction kinetics. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a preparation flow chart of the MgAl LDH / MXene two-dimensional composite material of the present invention;

[0030] Figure 2 is a morphology and structural characterization diagram of the MgAl LDH / MXene two-dimensional material prepared in Preparation Example 3 of the present invention, wherein Figure 2 a is the AFM image of MgAl LDH / MXene two-dimensional material, Figure 2 b is the thickness distribution diagram; Figure 2 c is the TEM image, Figure 2 d is the corresponding selected area electron diffraction pattern; Figure 2 e is the high-resolution transmission electron microscopy image and the energy spectrum of each element;

[0031] Figure 3(a) XRD and (b) FITR spectra of the MgAl LDH / MXene two-dimensional composite material prepared in Example 3 of the present invention and the MgAl LDH in Comparative Example 1 and the MXene material in Comparative Example 2;

[0032] Figure 4 is an X-ray photoelectron spectrum of the MgAl LDH / MXene two-dimensional composite material prepared in Example 3 of the present invention and the MgAl LDH in Comparative Example 1 and the MXene material in Comparative Example 2, wherein Figure 4 a is the full X-ray photoelectron spectrum of MgAl LDH / MXene two-dimensional composite material; Figure 4 b is the Ti 2p XPS spectrum of MgAl LDH / MXene; Figure 4 c is the Mg 1s XPS spectrum; d is the Al 2p XPS spectrum;

[0033] Figure 5 : is a visualized adsorption experimental diagram of the MgAl LDH / MXene two-dimensional composite material prepared in Example 3 of the present invention and the MgAl LDH in Comparative Example 1 and the MXene material in Comparative Example 2, wherein Figure 5 a is the visualization experimental diagram and UV-vis spectrum of the material after adding Li2S6 solution and standing for 24 hours; after the Li2S6 adsorption experiment, Figure 5 b is the XPS graph of Ti 2p of Mg Al LDH / MXene two-dimensional material, MgAl LDH material, MXene material and Li2S6; Figure 5 c is the Li 1s XPS graph after the Li2S6 adsorption experiment; Figure 5 d is the XPS graph of S2p after Li2S6 adsorption experiment;

[0034] Figure 6 is an illustration of the diaphragm barrier layer of the MgAl LDH / MXene two-dimensional composite material prepared in Example 3 of the present invention in Application Example 1, wherein Figure 6 a is a scanning electron microscope image of the cross-sectional thickness of the diaphragm barrier layer; Figure 6 b is a scanning electron microscope image of the surface of the diaphragm barrier layer, and the inset is a digital photo of the surface of the diaphragm barrier layer; Figure 6 c is the contact angle of the membrane barrier layer surface;

[0035] Figure 7 is a diagram describing the performance of a Li-Li symmetric battery assembled with the diaphragm barrier layer of the MgAl LDH / MXene two-dimensional composite material prepared in Example 3 of the present invention, wherein Figure 7 (ab) are lithium ion migration diagrams of Li-Li symmetric cells assembled with MgAl LDH / MXene two-dimensional composite separator barrier layer; Figure 7 (cd) are lithium ion transference diagrams of Li-Li symmetric cells assembled with pure PP separators not coated with MgAl LDH / MXene two-dimensional composite materials; Figure 7 e is the Li-Li symmetric cell at 1 mA cm -2 The cycle diagram below;

[0036] Figure 8 is a graph describing the performance of a lithium-sulfur battery assembled with the diaphragm barrier layer of the MgAl LDH / MXene two-dimensional composite material prepared in Example 3 of the present invention, wherein Figure 8 a is the rate cycle diagram; Figure 8 b is the impedance diagram; Figure 8 c is the long cycle diagram at 0.2C. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but they are not intended to limit the present invention.

[0038] Example 1. A method for preparing a two-dimensional composite material. 0.1 g of MXene is added to 100 mL of formamide, and ultrasonically dispersed for 30 minutes to obtain a MXene formamide dispersion. Then, 0.1 g of MgAl LDH is added to the 100 mL of MXene formamide dispersion, and magnetically stirred for 8 hours. The mixture is washed with anhydrous ethanol for 7 times, and vacuum dried at 40-80°C for 12 hours to obtain a two-dimensional composite material, which is recorded as MgAlLDH / MXene.

[0039] The MgAl LDH is prepared by the following method:

[0040] 0.5 g of magnesium aluminum hydrotalcite, 20 g of sodium chloride and 60 μL of 10 mol / L hydrochloric acid solution were added to 400 mL of deionized water, stirred magnetically for 20 h, washed with deionized water 7 times, and freeze-dried at -50 °C for 12 h to obtain MgAl-Cl - LDH powder;

[0041] 0.4 g MgAl-Cl - LDH and 6.5 g sodium nitrate were added to 400 mL deionized water, stirred for 12 h, washed with deionized water 7 times, and freeze-dried at -50 °C for 12 h to obtain MgAl-NO3 - LDH powder;

[0042] 0.1g MgAl-NO3 - Add 150 mL of formamide to LDH and perform ultrasonic stripping for 12 h to obtain MgAl LDH.

[0043] The MXene is prepared by the following method: at 2°C, 2g of lithium fluoride and 20mL of 10mol / L hydrochloric acid solution are placed in a polytetrafluoroethylene reactor, magnetically stirred for 15min, and then 2g of titanium carbide aluminum powder is added to the reactor within 25min. After etching for 0.5h, the temperature is raised to 30°C and reacted for 12h to obtain a mixed solution; the mixed solution is first pickled with 100mL of 0.5mol / L hydrochloric acid, centrifuged at a speed of 2500r / min for 0.5min, and then washed and centrifuged with deionized water under the same conditions until the pH value of the solution becomes 5, and the upper layer solution is first introduced with nitrogen for 0.5h, and under the protection of nitrogen, ice bath ultrasound is performed for 30min, and then centrifuged at a speed of 2500r / min for 0.5h, the upper layer liquid is collected, and freeze-dried at -50°C for 24h to finally obtain MXene.

[0044] Example 2: A method for preparing a two-dimensional composite material. 0.12 g of MXene was added to 120 mL of formamide, and ultrasonically dispersed for 45 minutes to obtain a MXene formamide dispersion. Then, 0.12 g of MgAl LDH was added to the 120 mL of MXene formamide dispersion, and magnetically stirred for 10 hours. The mixture was washed with anhydrous ethanol for 10 times, and vacuum dried at 50°C for 18 hours to obtain a two-dimensional composite material, which was recorded as MgAlLDH / MXene.

[0045] The MgAl LDH is prepared by the following method:

[0046] 0.56 g of magnesium aluminum hydrotalcite, 28.7 g of sodium chloride and 70 μL of 12 mol / L hydrochloric acid solution were added to 450 mL of deionized water, magnetically stirred for 22 h, washed with deionized water 8 times, and freeze-dried at -45 °C for 18 h to obtain MgAl-Cl - LDH powder;

[0047] 0.45 g MgAl-Cl - LDH and 7.5 g sodium nitrate were added to 450 mL deionized water, stirred for 18 h, washed with deionized water 8 times, and freeze-dried at -45 °C for 18 h to obtain MgAl-NO3 - LDH powder;

[0048] 0.16 g of MgAl-NO3 - 160 mL of formamide was added to LDH and ultrasonic stripping was performed for 18 h to obtain MgAl LDH.

[0049] The MXene is prepared by the following method: at 4°C, 2.5g of lithium fluoride and 25mL of 12mol / L hydrochloric acid solution are placed in a polytetrafluoroethylene reactor, magnetically stirred for 20min, and then 2.5g of titanium carbide aluminum powder is added to the reactor within 25min. After etching for 0.8h, the temperature is raised to 34°C and reacted for 18h to obtain a mixed solution; the mixed solution is first pickled with 100mL of 0.5mol / L hydrochloric acid, centrifuged at a speed of 3500r / min for 1min, and then washed and centrifuged with deionized water under the same conditions until the pH value of the solution becomes 5, and the upper layer solution is first introduced with nitrogen for 30h, and under the protection of nitrogen, ice bath ultrasound is performed for 40min, and then centrifuged at a speed of 3500r / min for 30h, the upper layer liquid is collected, and freeze-dried at -45°C for 36h to finally obtain MXene.

[0050] Example 3. A method for preparing a two-dimensional composite material. 0.16 g of MXene was added to 160 mL of formamide, and ultrasonically dispersed for 60 minutes to obtain a MXene formamide dispersion. Then, 0.16 g of MgAl LDH was added to the 160 mL of MXene formamide dispersion, and magnetically stirred for 12 hours. The mixture was washed with anhydrous ethanol for 12 times, and vacuum dried at 60°C for 24 hours to obtain a two-dimensional composite material, which was recorded as MgAlLDH / MXene.

[0051] The MgAl LDH is prepared by the following method:

[0052] 0.6 g of magnesium aluminum hydrotalcite, 32.9 g of sodium chloride and 85 μL of 12 mol / L hydrochloric acid solution were added to 450 mL of deionized water, magnetically stirred for 24 h, washed with deionized water 9 times, and freeze-dried at -45 °C for 24 h to obtain MgAl-Cl - LDH powder;

[0053] 0.5 g MgAl-Cl - LDH and 8.5 g sodium nitrate were added to 450 mL deionized water, stirred for 24 h, washed with deionized water 9 times, and freeze-dried at -45 °C for 24 h to obtain MgAl-NO3 - LDH powder;

[0054] 0.2g MgAl-NO3 - Add 200 mL of formamide to LDH and perform ultrasonic stripping for 24 h to obtain MgAl LDH.

[0055] The MXene is prepared by the following method: at 3°C, 30 mL of 12 mol / L hydrochloric acid solution of 3 g lithium fluoride is placed in a polytetrafluoroethylene reactor, magnetically stirred for 30 minutes, and then 3 g of titanium carbide aluminum powder is added to the reactor within 30 minutes. After etching for 1 hour, the temperature is raised to 36°C and reacted for 24 hours to obtain a mixed solution; the mixed solution is firstly pickled with 150 mL of 1 mol / L hydrochloric acid, centrifuged at a speed of 3500 r / min for 1 minute, and then washed and centrifuged with deionized water under the same conditions until the pH value of the solution becomes 7, and the upper layer solution is first introduced with nitrogen for 1 hour, and under the protection of nitrogen, ice bath ultrasound is performed for 50 minutes, and then centrifuged at a speed of 3500 r / min for 1 hour, the upper layer liquid is collected, and freeze-dried at -40°C for 48 hours to finally obtain MXene.

[0056] Example 4: A method for preparing a two-dimensional composite material. 0.18 g of MXene was added to 180 mL of formamide, and ultrasonically dispersed for 80 min to obtain a MXene formamide dispersion. Then, 0.18 g of MgAl LDH was added to the 180 mL of MXene formamide dispersion, and magnetically stirred for 14 h. The mixture was washed with anhydrous ethanol for 14 times, and vacuum dried at 70 °C for 30 h to obtain a two-dimensional composite material, which was recorded as MgAlLDH / MXene.

[0057] The MgAl LDH is prepared by the following method:

[0058] 0.7 g of magnesium aluminum hydrotalcite, 40 g of sodium chloride and 95 μL of 12 mol / L hydrochloric acid solution were added to 450 mL of deionized water, stirred magnetically for 25 h, washed with deionized water 11 times, and freeze-dried at -35 °C for 36 h to obtain MgAl-Cl - LDH powder;

[0059] 0.55 g MgAl-Cl - LDH and 9.5 g sodium nitrate were added to 450 mL deionized water, stirred for 30 h, washed with deionized water 11 times, and freeze-dried at -35 °C for 30 h to obtain MgAl-NO3 - LDH powder;

[0060] 0.25 g of MgAl-NO3 - LDH was added with 200 mL of formamide and subjected to ultrasonic stripping for 30 h to obtain MgAl LDH.

[0061] The MXene is prepared by the following method: at 4°C, 3.5g of lithium fluoride and 35mL of 12mol / L hydrochloric acid solution are placed in a polytetrafluoroethylene reactor, magnetically stirred for 40min, and then 3.5g of titanium carbide aluminum powder is added to the reactor within 30min. After etching for 1.2h, the temperature is raised to 40°C and reacted for 36h to obtain a mixed solution; the mixed solution is first pickled with 180mL of 1mol / L hydrochloric acid, centrifuged at 4000r / min for 1min, and then washed and centrifuged with deionized water under the same conditions until the pH value of the solution becomes 7, and the upper layer solution is first introduced with nitrogen for 1.5h, and under the protection of nitrogen, ice bath ultrasound is performed for 70min, and then centrifuged at 4000r / min for 1.5h, the upper layer liquid is collected, and freeze-dried at -35°C for 60h to finally obtain MXene.

[0062] Example 5. A method for preparing a two-dimensional composite material: add 0.2 g of MXene to 200 mL of formamide, ultrasonically disperse for 90 minutes to obtain a MXene formamide dispersion, then add 0.2 g of MgAl LDH to the 200 mL of MXene formamide dispersion, magnetically stir for 15 hours, wash with anhydrous ethanol 15 times, and vacuum dry at 80°C for 36 hours to obtain a two-dimensional composite material, recorded as MgAl LDH / MXene.

[0063] The MgAl LDH is prepared by the following method:

[0064] 0.8 g of magnesium aluminum hydrotalcite, 45 g of sodium chloride and 100 μL of 15 mol / L hydrochloric acid solution were added to 500 mL of deionized water, stirred magnetically for 28 h, washed with deionized water 12 times, and freeze-dried at -30 °C for 48 h to obtain MgAl-Cl - LDH powder;

[0065] 0.6 g MgAl-Cl - LDH and 10.5 g sodium nitrate were added to 500 mL deionized water, stirred for 36 h, washed with deionized water 12 times, and freeze-dried at -30 ° C for 36 h to obtain MgAl-NO3 - LDH powder;

[0066] 0.3 g of MgAl-NO3 - Add 250 mL of formamide to LDH and perform ultrasonic stripping for 36 h to obtain MgAl LDH.

[0067] The MXene is prepared by the following method: at 5°C, 4g of lithium fluoride and 40mL of 15mol / L hydrochloric acid solution are placed in a polytetrafluoroethylene reactor, magnetically stirred for 45min, and then 4g of titanium carbide aluminum powder is added to the reactor within 35min. After etching for 1.5h, the temperature is raised to 45°C and reacted for 48h to obtain a mixed solution; the mixed solution is first pickled with 200mL of 1.5mol / L hydrochloric acid, centrifuged at 4500r / min for 2min, and then washed and centrifuged with deionized water under the same conditions until the pH value of the solution becomes 7, the upper layer solution is first introduced with nitrogen for 2h, and under the protection of nitrogen, ice bath ultrasound is performed for 80min, and then centrifuged at 4500r / min for 2h, the upper layer liquid is collected, and freeze-dried at -30°C for 72h to finally obtain MXene.

[0068] Application Example 1:

[0069] The MgAl LDH / MXene two-dimensional composite material prepared in Examples 1-5 is used for the barrier layer of the lithium-sulfur battery separator. First, the MgAl LDH / MXene two-dimensional composite material prepared in Examples 1-5, the conductive agent Keqian Black (KB), and the binder PVDF are added to the NMP solvent in a ratio of 4:5:1 for grinding, and then the slurry is applied to the PP separator, and after vacuum drying for 24 hours, it is cut into discs with a 16mm cutter to obtain the MgAl LDH / MXene PP separator. The separator is used for the barrier layer of the lithium-sulfur battery separator.

[0070] Comparative Example 1: MgAl LDH was prepared by the following method:

[0071] 0.6 g of magnesium aluminum hydrotalcite, 32.9 g of sodium chloride and 85 μL of 12 mol / L hydrochloric acid solution were added to 450 mL of deionized water, magnetically stirred for 24 h, washed with deionized water 9 times, and freeze-dried at -45 °C for 24 h to obtain MgAl-Cl - LDH powder;

[0072] 0.5 g MgAl-Cl - LDH and 8.5 g sodium nitrate were added to 450 mL deionized water, stirred for 24 h, washed with deionized water 9 times, and freeze-dried at -45 °C for 24 h to obtain MgAl-NO3 - LDH powder;

[0073] 0.2g MgAl-NO3 - LDH was added with 200 mL of formamide and subjected to ultrasonic stripping for 24 h to obtain MgAl LDH, which was then washed with anhydrous ethanol for 7 times and dried under vacuum at 60 °C for 12 h to obtain MgAl LDH.

[0074] Comparative Example 2: MXene was prepared by the following method: at 3°C, 3g of lithium fluoride and 30mL of 12mol / L hydrochloric acid solution were placed in a polytetrafluoroethylene reactor, and the reaction was stirred magnetically for 30min. Then, 3g of titanium carbide aluminum powder was added to the reactor within 30min. After etching for 1h, the temperature was raised to 36°C and reacted for 24h to obtain a mixed solution. The mixed solution was first pickled with 150mL of 1mol / L hydrochloric acid, centrifuged at 3500r / min for 1min, and then washed and centrifuged with deionized water under the same conditions until the pH value of the solution became 7. The upper layer solution was first introduced with nitrogen for 1h, and under the protection of nitrogen, ice bath ultrasound was performed for 50min, and then centrifuged at 3500r / min for 1h. The upper layer liquid was collected and freeze-dried at -40°C for 48h to finally obtain MXene.

[0075] Experimental proof:

[0076] 1. Figure 1 This is a flow chart for preparing the MgAl LDH / MXene two-dimensional composite material of the present invention. As shown in the figure, the magnesium aluminum hydrotalcite and titanium carbide aluminum powder are three-dimensional layered structures before treatment, and are two-dimensional lamellar structures after treatment. The detailed process is shown in Examples 1 to 5.

[0077] 2. Figure 2 is a morphology and structural characterization diagram of the MgAl LDH / MXene two-dimensional material prepared in Preparation Example 3 of the present invention, wherein Figure 2 a is the AFM image of MgAl LDH / MXene two-dimensional material, Figure 2 b is the thickness distribution diagram; Figure 2 c is the TEM image, Figure 2 d is the corresponding selected area electron diffraction pattern; Figure 2 e is the high-resolution transmission electron microscopy image and the energy spectrum of each element; AFM image ( Figure 2 a) shows the two-dimensional morphology of MgAl LDH / MXene. The height distribution in the inset shows that the thickness of MgAl LDH / MXene is 6-7 nm ( Figure 2 b). The morphology and structure of the samples were characterized by transmission electron microscopy (TEM). Figure 2 As shown in Figure c, MgAlLDH / MXene exhibits a layered morphology, uniform dispersion, and no obvious stacking. Among them, MgAl LDH is in a regular small round shape, while MXene is irregular in shape. The selected area electron diffraction (SAED) pattern shows that MgAl LDH / MXene is composed of MgAl LDH (018) and MXene (010) ( Figure 2 d). High-resolution TEM elemental mapping ( Figure 2e) The results show the uniform distribution of Ti, F, O, Mg, and Al elements in MgAl LDH / MXene. The results show that the MgAl LDH / MXene two-dimensional material was successfully synthesized.

[0078] 3. Figure 3 The (a) XRD and (b) FITR spectra of the MgAl LDH / MXene two-dimensional composite material prepared in Example 3 of the present invention and the MgAl LDH in Comparative Example 1 and the MXene material in Comparative Example 2; XRD tests were performed on the MgAl LDH / MXene prepared in Example 3 and the MgAl LDH in Comparative Example 1 and the MXene material in Comparative Example 2, as shown in FIG. Figure 3 As shown in a. MXene shows a characteristic (002) peak at 5.6°, and other diffraction peaks are located at 60.5°, corresponding to the (110) crystal plane. The spectrum of MgAl LDH shows characteristic peaks at 11.5°, 23.2°, 34.5°, 38.8°, 46.0°, 60.7°, and 62.0°, which are marked as (003), (006), (009), (012), (015), (110), and (113) crystal planes, respectively. The XRD spectrum of MgAl LDH / MXene shows all the typical peaks of MgAl LDH and MXene, indicating that the MgAl LDH / MXene two-dimensional composite material has been successfully synthesized. Figure 3 b shows the FTIR spectra of MXene, MgAl LDH, and MgAl LDH / MXene. For MgAl LDH, 3465, 1630, 1370, and 451 cm -1 The absorption peaks at are considered to be -OH, HOH, and NO3 of MgAl LDH. - , and Mg-OH(Al-OH). In the spectrum of MXene, 3450, 1640, 670 cm -1 The bands at correspond to -OH, C=O, and Ti-O. Note that all characteristic peaks of MgAl LDH appear in the FTIR spectrum of MgAlLDH / MXene. However, in MgAl LDH / MXene, the FTIR characteristic peaks of MXene are not obvious, which means that MgAl LDH covers the surface of MXene.

[0079] 4. Figure 4 is an X-ray photoelectron spectrum of the MgAl LDH / MXene two-dimensional composite material prepared in Example 3 of the present invention and the MgAl LDH in Comparative Example 1 and the MXene material in Comparative Example 2, wherein Figure 4 a is the full X-ray photoelectron spectrum of MgAl LDH / MXene two-dimensional composite material; Figure 4b is the Ti 2p XPS spectrum of MgAl LDH / MXene; Figure 4 c is the Mg 1s XPS spectrum; d is the Al 2p XPS spectrum; X-ray photoelectron spectroscopy (XPS) spectra are used to further understand the interaction between MgAl LDH and MXene. The presence of Mg, Al, N, Ti, and F elements can be confirmed by measuring the full X-ray photoelectron spectrum ( Figure 2 e), which is consistent with the well-known major elements in MgAl LDH and MXene revealed by high-resolution TEM elemental mapping. High-resolution Ti 2p spectrum ( Figure 4 b) consists of four double peaks, corresponding to Ti-C (454.69 and 455.09 eV), Ti 2+ (455.13 and 455.56 eV), Ti 3+ (456.88 and 457.32 eV), Ti-O (458.51 and 459.0 eV). Compared with the Ti 2p XPS spectrum of MXene, the downward shift of the MgAl LDH / MXene absorption peak is attributed to the electron transfer between Mg Al LDH and MXene; high-resolution Mg 1s and Al 2p XPS spectra such as Figure 4 As shown in (c, d), the binding energies of Al 2p and Mg 1s increased from 1304.03 and 74.38 eV for MgAl LDH and 1304.18 and 74.78 eV for MgAl LDH / MXene, respectively. The absorption peaks of Mg 1s and Al 2p shifted upward, indicating the interaction between MgAl LDH and MXene.

[0080] 5. Figure 5 : is a visualized adsorption experimental diagram of the MgAl LDH / MXene two-dimensional composite material prepared in Example 3 of the present invention and the MgAl LDH in Comparative Example 1 and the MXene material in Comparative Example 2, wherein Figure 5 a is the visualization experimental diagram and UV-vis spectrum of the material after adding Li2S6 solution and standing for 24 hours; after the Li2S6 adsorption experiment, Figure 5 b is the XPS graph of Ti 2p of Mg Al LDH / MXene two-dimensional material, MgAl LDH material, MXene material and Li2S6; Figure 5 c is the Li 1s XPS graph after the Li2S6 adsorption experiment; Figure 5 d is the XPS graph of S2p after the Li2S6 adsorption experiment; In order to study the adsorption capacity of MgAl LDH / MXene for polysulfide, Li2S6 solution (3 mmol L -1) was added with 20 mg MgAl LDH / MXene, MgAl LDH, and MXene for visual adsorption test ( Figure 5 a). After 24 h of static adsorption, MgAl LDH / MXene was completely transparent, while MgAl LDH / MXenes containing MXene were light yellow, indicating that MgAl LDH / MXne and MgAl LDH had excellent adsorption capacity, which was attributed to the strong interaction between the positively charged layer and the Mg Al LDH containing rich hydroxyl groups and LiPSs, which was consistent with the UV-visible spectrum (UV-vis). The chemical interaction between MgAl LDH / MXene and LiPSs was further studied by XPS. High-resolution Ti 2p XPS spectrum of MgAlLDH / MXene ( Figure 5 b) shows that there are four pairs of peaks before Li2S6 adsorption. These characteristic peaks move to lower binding energy after adsorption, and a pair of new peaks appear at 457.13eV and 464.68eV, indicating that there is a Ti-S bond between MgAlLDH / MXene and LiPSs, and MgAl LDH / MXene has a strong chemical interaction with LiPSs. The high-resolution Li 1s XPS spectrum of MgAl LDH / MXene is shown in Figure 2. Figure 5 As shown in c, compared with the blank sample of Li2S6, new Li-O bonds were found in all samples (including MgAl LDH / MXene, MgAl LDH, MXene), indicating that the -OH on MgAl LDH and the oxygen-containing end groups on MXene are helpful to establish chemical interactions with LiPSs. In addition, the high-resolution S2p XPS spectrum ( Figure 5 d) also shows that MgAl LDH / MXene has a strong chemical affinity for polysulfides based on the appearance of S-Ti bonds at 161.93 eV.

[0081] 6. Figure 6 is an illustration of the diaphragm barrier layer of the MgAl LDH / MXene two-dimensional composite material prepared in Example 3 of the present invention in Application Example 1, wherein Figure 6 a is a scanning electron microscope image of the cross-sectional thickness of the diaphragm barrier layer; Figure 6 b is a scanning electron microscope image of the surface of the diaphragm barrier layer, and the inset is a digital photo of the surface of the diaphragm barrier layer; Figure 6 c is the contact angle of the membrane barrier layer surface; Figure 6 It can be seen from a that the thickness of the diaphragm barrier layer is very thin, 5.5 μm, and the surface of the commercial PP diaphragm is evenly covered (such as Figure 6 b), the coating surface is relatively smooth and dense, which is related to its good rate performance. Figure 6c It can be seen that the separator barrier layer has excellent electrolyte wettability.

[0082] 7. Figure 7 is a diagram describing the performance of a Li-Li symmetric battery assembled with the diaphragm barrier layer of the MgAl LDH / MXene two-dimensional composite material prepared in Example 3 of the present invention, wherein Figure 7 (ab) are lithium ion migration diagrams of Li-Li symmetric cells assembled with MgAl LDH / MXene two-dimensional composite separator barrier layer; Figure 7 (cd) are lithium ion transference diagrams of Li-Li symmetric cells assembled with pure PP separators not coated with Mg Al LDH / MXene two-dimensional composite materials; Figure 7 e is the Li-Li symmetric cell at 1 mA cm -2 The following cycle diagram; Figure 7 The lithium ion transfer number (t Li+ ), which represents the ratio of the mobility of lithium ions in the electrolyte to the sum of the mobility of all ions. The barrier layer of the two-dimensional composite separator has a maximum t of 0.67 Li+ , while the t of pure PP Li+ Only 0.49( Figure 7 c and 7d), which may be due to the abundant surface oxygen-containing groups on the surface of MgAl LDH and MXene promoting the dissociation of lithium salts. Figure 7 In e, a Li-Li symmetric cell assembled with MgAl LDH / MXene and PP separator was tested at 1 mA cm -2 Voltage-time curves at current densities of 1.5 Å and 2.5 Å. It can be seen that in the initial stage, both exhibited large overpotentials. As lithium deposition progresses, the overpotential of the Li-Li symmetric cell assembled with the Mg Al LDH / MXene two-dimensional composite separator barrier layer decreases slowly and steadily, eventually maintaining a stable voltage and exhibiting a narrower overpotential than the original PP separator, indicating that the growth of lithium dendrites is significantly suppressed.

[0083] 8. Figure 8 is a graph describing the performance of a lithium-sulfur battery assembled with the diaphragm barrier layer of the MgAl LDH / MXene two-dimensional composite material prepared in Example 3 of the present invention, wherein Figure 8 a is the rate cycle diagram; Figure 8 b is the impedance diagram; Figure 8 c is the long cycle diagram at 0.2C; Figure 8As shown in a, a lithium-sulfur battery was assembled with a MgAl LDH / MXene two-dimensional composite material separator barrier layer to test its rate performance. The battery using the MgAl LDH / MXene separator barrier layer provided 1159.2, 1015.73, 929.6, 859.0, and 810.9 mAh g at 0.2C, 0.5C, 1C, 2C, and 3C, respectively. -1 When the current was switched back to 0.2C, the discharge capacity recovered to 1033.8 mAh g -l , and the rate performance is much higher than that of the original PP separator, which means that the MgAl LDH / MXene two-dimensional composite material promotes the fast redox reaction kinetics and excellent electrochemical reversibility of polysulfides. The impedance diagram of the battery was obtained by electrochemical impedance spectroscopy (EIS) measurement. Figure 8 As shown in (b), the semicircle in the high-frequency region and the straight line in the medium-high-frequency region correspond to the charge transfer resistance (Rct) and the Warburg resistance, respectively. It is worth noting that the battery using MgAl LDH / MXene has a smaller impedance (26.5Ω) compared with the battery using PP (41Ω), which is attributed to the high conductivity of MXene and the fast Li + Transfer capacity. The battery using MgAl LDH / MXene at 0.2C ( Figure 8 c) has 1059.45 mAh g -1 The high initial discharge capacity of 857.90 mAh g-1 was maintained after 100 cycles. -l , better than the original PP (850mAh g -1 , 2.48%). This evidence suggests that the battery assembled with the MgAl LDH / MXene 2D composite separator barrier layer improves the sulfur utilization and enhances the conversion of polysulfides.

[0084] The applicant also carried out the above-mentioned preparation of MgAl LDH / MXene two-dimensional composite materials in other embodiments. Figure 2-8 The experimental tests and analyses described herein yielded results comparable to those of the tests and analyses described above.

Claims

1. A method for preparing a two-dimensional composite material, characterized in that: MXene was added to formamide and ultrasonically dispersed to obtain a MXene formamide dispersion. MgAl LDH was then added to the MXene formamide dispersion, magnetically stirred, washed with anhydrous ethanol, and vacuum dried to obtain a two-dimensional composite material, which was recorded as MgAl LDH / MXene.

2. The method for preparing a two-dimensional composite material according to claim 1, characterized in that: 0.1-0.2 g MXene is added to 100-200 mL formamide, and ultrasonic dispersion is performed for 30-90 min to obtain a MXene formamide dispersion. Then, 0.1-0.2 g MgAl LDH is added to the 100-200 mL MXene formamide dispersion, and magnetic stirring is performed for 8-15 h. The mixture is washed with anhydrous ethanol for 7-15 times, and vacuum dried at 40-80 ° C for 12-36 h to obtain a two-dimensional composite material, which is recorded as MgAl LDH / MXene.

3. The method for preparing a two-dimensional composite material according to claim 1, characterized in that: 0.16 g of MXene was added to 160 mL of formamide, and ultrasonic dispersion was performed for 60 min to obtain a MXene formamide dispersion. Then, 0.16 g of MgAl LDH was added to the 160 mL of MXene formamide dispersion, and magnetic stirring was performed for 12 h. The mixture was washed with anhydrous ethanol for 12 times, and vacuum dried at 60° C. for 24 h to obtain a two-dimensional composite material, which was recorded as MgAl LDH / MXene.

4. The method for preparing a two-dimensional composite material according to claim 1, characterized in that: The MgAlLDH is prepared by the following method: 0.5-0.8 g of magnesium aluminum hydrotalcite, 20-45 g of sodium chloride and 60-100 μL of 10-15 mol / L hydrochloric acid solution were added to 400-500 mL of deionized water, stirred magnetically for 20-28 h, washed with deionized water for 7-12 times, and freeze-dried at -50--30 ° C for 12-48 h to obtain MgAl-Cl - LDH powder; 0.4-0.6 g MgAl-Cl - LDH and 6.5-10.5 g sodium nitrate were added to 400-500 mL deionized water, stirred for 12-36 h, washed with deionized water 7-12 times, and freeze-dried at -50--30 °C for 12-36 h to obtain MgAl-NO3 - LDH powder; 0.1~0.3g MgAl-NO3 - Add 150-250 mL of formamide to LDH and perform ultrasonic stripping for 12-36 h to obtain MgAlLDH.

5. The method for preparing a two-dimensional composite material according to claim 4, characterized in that: The MgAlLDH is prepared by the following method: 0.6 g of magnesium aluminum hydrotalcite, 32.9 g of sodium chloride and 85 μL of 12 mol / L hydrochloric acid solution were added to 450 mL of deionized water, magnetically stirred for 24 h, washed with deionized water 9 times, and freeze-dried at -45 °C for 24 h to obtain MgAl-Cl - LDH powder; 0.5 g MgAl-Cl - LDH and 8.5 g sodium nitrate were added to 450 mL deionized water, stirred for 24 h, washed with deionized water 9 times, and freeze-dried at -45 °C for 24 h to obtain MgAl-NO3 - LDH powder; 0.2g MgAl-NO3 - LDH was added with 200 mL of formamide and subjected to ultrasonic stripping for 24 h to obtain MgAlLDH.

6. The method for preparing a two-dimensional composite material according to claim 1, characterized in that: The MXene is prepared by the following method: at 2 to 5° C., 2 to 4 g of lithium fluoride and 20 to 40 mL of 10 to 15 mol / L hydrochloric acid solution are placed in a polytetrafluoroethylene reactor, and reacted by magnetic stirring for 15 to 45 min. Then, 2 to 4 g of titanium carbide aluminum powder is added to the reactor within 25 to 35 min. After etching for 0.5 to 1.5 h, the temperature is raised to 30 to 45° C., and the mixture is reacted for 12 to 48 h to obtain a mixed solution. The mixed solution is firstly heated with 100 to 200 mL of 0.5 to 1.5 mol / L hydrochloric acid pickling, centrifugation at a speed of 2500-4500r / min for 0.5-2min, then washing and centrifugation with deionized water under the same conditions until the pH value of the solution becomes 5-7, nitrogen is introduced into the upper solution for 0.5-2h, and ice bath ultrasound is performed for 30-80min under the protection of nitrogen, and then centrifugation at a speed of 2500-4500r / min for 0.5-2h, the upper liquid is collected, and freeze-dried at -50--30℃ for 24-72h to finally obtain MXene.

7. The method for preparing a two-dimensional composite material according to claim 6, characterized in that: The MXene is prepared by the following method: at 3°C, 30 mL of 12 mol / L hydrochloric acid solution of 3 g lithium fluoride is placed in a polytetrafluoroethylene reactor, magnetically stirred for 30 minutes, and then 3 g of titanium carbide aluminum powder is added to the reactor within 30 minutes. After etching for 1 hour, the temperature is raised to 36°C and reacted for 24 hours to obtain a mixed solution; the mixed solution is firstly pickled with 150 mL of 1 mol / L hydrochloric acid, centrifuged at a speed of 3500 r / min for 1 minute, and then washed and centrifuged with deionized water under the same conditions until the pH value of the solution becomes 7, and the upper layer solution is first introduced with nitrogen for 1 hour, and under the protection of nitrogen, ice bath ultrasound is performed for 50 minutes, and then centrifuged at a speed of 3500 r / min for 1 hour, the upper layer liquid is collected, and freeze-dried at -40°C for 48 hours to finally obtain MXene.

8. Use of the two-dimensional composite material according to any one of claims 1 to 7, characterized in that: The two-dimensional composite material is used for a lithium-sulfur battery separator barrier layer to suppress the shuttle effect of polysulfides.

Citation Information

Cited By

  • Asparagus tailing-based material for hexavalent chromium reduction and preparation method of asbestos tailing-based material

    CN122076398A

  • An asbestos tailings-based material for hexavalent chromium reduction and a method of preparing the same

    CN122076398B